Musculoskeletal disorders among health workers of a private clinic of Lima city: Musculoskeletal disorders among health workers of a private clinic of Lima city - Ballena-Ramos, Aimee (2021)
Objective: To determine the frequency of musculoskeletal disorders in health workers of a private clinic in Lima. Materials and methods: This research has a quantitative approach, a non-experimental, descriptive and cross-sectional design. Data collection was carried out by means of the survey technique using the Nordic Kuorinka Questionnaire. Results: Of the 300 participants, 72.7% (n = 218) were women and the rest were men. Technical personnel and nurses participated in a higher proportion, with a frequency of 56% (n = 168) and 22% (n = 66), respectively. Regarding pain, discomfort or discomfort presented at some point during the last twelve months, the areas with the greatest involvement were the cervical, dorsal and lumbar region, with a frequency of 76.7% (n = 231), 73.7% ( n = 221) and 70.3% (n = 211), respectively. Interferences with home or work tasks due to the problem were mainly caused by the involvement of the cervical, lumbar and dorsal regions, with 51% (n = 153), 50.7% (n = 152) and 45.3 % (n = 136), respectively. The presence of these problems during the last seven days occurred mainly in the dorsal, lumbar and cervical region, with a frequency of 60.3% (n = 181), 53.3% (n = 160) and 46% (n = 138), respectively. Women had a higher frequency compared to men in the dorsal (p = 0.029), lumbar (p = 0.018) region. Conclusions: Musculoskeletal disorders in health workers are very common, especially affecting the dorsal, lumbar, and cervical region. It is recommended to promote actions that prevent health personnel from triggering an occupational disease. Keywords: Musculoskeletal Pain; Health personnel; Occupational health; Ergonomics; Peru (Source: DeCS, BIREME).